1999
DOI: 10.1007/s002130051087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reinforcing properties and phencyclidine-like discriminative stimulus effects of dextromethorphan and dextrorphan in rats and rhesus monkeys

Abstract: Taken together, these data show that DXM has some PCP-like effects in rats and monkeys, but that they are more reliably produced by its metabolite, DXO. Thus, high doses of DXM may have some PCP-like abuse potential in humans but this potential may be associated with, or enhanced by, metabolism of DXM to DXO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…These results are consistent with and extend the results of a recently published study in which a 30 mg/kg dose of dextromethorphan (s.c.) did not substitute for nicotine and did not antagonize nicotine's discriminative stimulus effects (Zakharova et al, 2005). Other research has shown that dextromethorphan and dextrorphan, both administered i.p., fully and dose-dependently substituted for the noncompetitive NMDA open channel blocker phencyclidine in rats (Nicholson et al, 1999). With s.c. administration, however, only dextrorphan substituted fully for phencyclidine, with dextromethorphan producing only partial substitution (Nicholson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with and extend the results of a recently published study in which a 30 mg/kg dose of dextromethorphan (s.c.) did not substitute for nicotine and did not antagonize nicotine's discriminative stimulus effects (Zakharova et al, 2005). Other research has shown that dextromethorphan and dextrorphan, both administered i.p., fully and dose-dependently substituted for the noncompetitive NMDA open channel blocker phencyclidine in rats (Nicholson et al, 1999). With s.c. administration, however, only dextrorphan substituted fully for phencyclidine, with dextromethorphan producing only partial substitution (Nicholson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that dextromethorphan and dextrorphan, both administered i.p., fully and dose-dependently substituted for the noncompetitive NMDA open channel blocker phencyclidine in rats (Nicholson et al, 1999). With s.c. administration, however, only dextrorphan substituted fully for phencyclidine, with dextromethorphan producing only partial substitution (Nicholson et al, 1999). These results suggest that NMDA antagonism cannot fully account for the stimulus properties of dextromethorphan when metabolism to dextrorphan is attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, dextromethorphan is a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist (Church et al, 1985;Church et al, 1989;Franklin and Murray, 1992). In rats and monkeys, dextromethorphan produces discriminate stimuli that generalize to phencyclidine (PCP) and other noncompetitive NMDA receptor antagonists (Holtzman, 1994;Nicholson et al, 1999). Like other noncompetitive NMDA receptor antagonists, such as PCP, dextromethorphan produces ataxia, and stereotypy in rats (Székely et al, 1991;Ishmael et al, 1998) and psychotomimetic and ethanollike effects and is subject to abuse in humans (Jasinski et al, 1971;Fleming, 1986;Orrell and Campbell, 1986;Mortimer et al, 1989;Bem and Peck, 1992;Steinberg et al, 1996;Soyka et al, 2000).…”
mentioning
confidence: 99%